Structural Determinants of Health: Towards a Political Economy of Health Perspective for Nursing - McGibbon, Elizabeth (Witness: The Canadian Journal of Critical Nursing Discourse, 2024)
This Invited Commentary focuses on a brief summary of how structural determinants of health (DoH) are framed in nursing and how a focus on the political economy of health can support identifying and addressing the ideological drivers of the structural DoH. Structural determinants focus on the politics and histories of enduring root causes of preventable injustices. There is a nascent literature in nursing regarding the structural DoH, which includes policy and governance processes, interlocking systems of oppression and discrimination, and social and economic structures that contribute to forces of power inherent in financial, legal, and governmental systems and policies. However, it is also crucially important to name and analyze their root ideological foundations because this is the space where structural change must be targeted. Various ideologies, intentionally or unintentionally, drive policy, politics, institutional governance and decision-making, and so on. The political economy of health is a foundational field that supports identifying these ideological drivers of the structural DoH. The invited commentary concludes with reflections and recommendations for nursing.